The roughening kinetics of hydrogenated graphene - Son, S.; Nunes, J. Figueira; Shin, Y.; Lee, J. H.; Casiraghi, C. (Scientific Reports, 2018)
The roughness is a common property of all growing surfaces - however, the way the roughness of a growing surface changes with time and space is uniquely related to the underlying growth process, i.e. to how the atoms stick to the surface during the first stage of nucleation. This concept allows getting insights on the nucleation process of a growing surface by measuring two scaling exponents, α and β, known as roughness and growth exponents, respectively. In this work, we studied hydrogenation of graphene using the roughening kinetics. The coverage of graphene will depend on how the H ions stick on the surface, giving rise to a unique roughness evolution in time and space. We measured a roughness exponent of ~0.5 (derived from a Fourier index of ~3), and a growth exponent of ~0.3. The values of the growth and roughness exponents are close to those reported for clustered carbon, suggesting a roughening mechanism by clustering, in good agreement with the theory. We also compared our coverage data with a different model, used to describe the dynamics of graphene coverage, during chemical vapour deposition. Our data are in agreement with a nucleation-dominated growth, further confirming that hydrogenation is happening by clustering.